Kontribusi Pesantren Terhadap Penguatan Dakwah Moderat Di Indonesia - Syarif Syammari. M; Yendri M. Fadly; Ridwal Trisoni; Muhamad Yahya (Al-Qolamuna: Journal Komunikasi dan Penyiaran Islam, 2025)
As the oldest Islamic educational institutions in the archipelago, Islamic boarding schools (pesantren) have a significant influence in shaping the religious practices of Indonesian society. They serve not only as centers for the teaching of Islamic knowledge but also as agents of ongoing moral, social, and cultural development. This article aims to analyze the role of pesantren in strengthening moderate da'wah practices in Indonesia through the educational process, the formation of the students' personalities, and community empowerment activities oriented toward the values ​​of welfare. This research uses a qualitative method with a literature review approach, drawing on various academic sources, pesantren institutional documents, and relevant previous research findings. This approach was chosen to gain a comprehensive understanding of pesantren's contribution to strengthening moderate da'wah, both theoretically and practically. Data were analyzed descriptively and analytically to uncover the patterns, strategies, and values ​​developed by pesantren in the context of Islamic da'wah in Indonesia. The study's findings indicate that pesantren function as centers for the dissemination of wasathiyah Islamic values, which emphasize tolerance, balance, inclusiveness, and openness to differences. The role of the kiai (Islamic scholars) as central figures and the santri (students) as agents of da'wah (Islamic outreach) are key to instilling these values ​​through the teaching of Islamic texts, exemplary morals, da'wah activities, and community programs. Furthermore, the ability of Islamic boarding schools (pesantren) to adapt to developments in information technology, such as the use of digital media and social platforms, has helped expand the reach of moderate da'wah amidst the challenges of globalization. Thus, Islamic boarding schools have proven to contribute significantly to supporting the strengthening of moderate da'wah and maintaining interfaith harmony in Indonesia. Abstrak Sebagai institusi pendidikan Islam tertua di Nusantara, pesantren memiliki pengaruh yang sangat besar dalam membentuk pola keberagamaan masyarakat Indonesia. Keberadaan pesantren tidak hanya berfungsi sebagai pusat pengajaran ilmu-ilmu keislaman, tetapi juga sebagai agen pembinaan moral, sosial, dan budaya yang berkelanjutan. Artikel ini bertujuan untuk menganalisis peran pesantren dalam memperkokoh praktik dakwah moderat di Indonesia melalui proses pendidikan, pembentukan kepribadian santri, serta kegiatan pemberdayaan umat yang berorientasi pada nilai-nilai kemaslahatan. Penelitian ini menggunakan metode kualitatif dengan pendekatan telaah pustaka terhadap berbagai sumber akademik, dokumen kelembagaan pesantren, serta hasil-hasil penelitian terdahulu yang relevan. Pendekatan ini dipilih untuk memperoleh pemahaman yang komprehensif mengenai kontribusi pesantren dalam penguatan dakwah moderat, baik dari aspek teoretis maupun praktis. Data dianalisis secara deskriptif-analitis guna mengungkap pola, strategi, dan nilai-nilai yang dikembangkan pesantren dalam konteks dakwah Islam di Indonesia. Hasil kajian menunjukkan bahwa pesantren berfungsi sebagai pusat penyebaran nilai-nilai Islam wasathiyah yang menekankan sikap toleran, seimbang, inklusif, dan terbuka terhadap perbedaan. Peran kiai sebagai figur sentral dan santri sebagai agen dakwah menjadi kunci utama dalam menanamkan nilai-nilai tersebut melalui pengajaran kitab keislaman, keteladanan akhlak, aktivitas dakwah, serta program-program kemasyarakatan. Selain itu, kemampuan pesantren dalam beradaptasi dengan perkembangan teknologi informasi, seperti pemanfaatan media digital dan platform sosial, turut memperluas jangkauan dakwah moderat di tengah tantangan globalisasi. Dengan demikian, pesantren terbukti berkontribusi nyata dalam mendukung penguatan dakwah moderat serta menjaga kerukunan dan harmoni umat beragama di Indonesia